Effects of Electronic Communication on 2023 National Election Break In Ogun State, Nigeria Tertiary Institutions - Ojetola Adetola Afolabi; Sesan-Aina Mojisola; Adenuga Olusegun; Onaopepo Ibrahim Bamidele; Adeleye Oluwafunmito Toluwalope (Britain International for Academic Research (BIAR-Publisher), 2025)
Communication and electronic media go hand in hand. In today’s technology-oriented world the use of electronic communication is inevitable. The role and importance of electronic communication cannot be overlooked. Electronic information interchange is necessary for today’s everyday survival. Information has severally been said to be the backbone of the economy of a nation. And the electronic media, being the main channels of information dissemination, has improved communication in numerous ways. The objective of this study is to assess the effectiveness of electronic communication on 2023 Election break in Ogun State, Nigeria. Technological determinism theory was used to provide theoretical background for this study. The study also utilized quantitative research method with survey method of collection of data with the aid of google form questionnaire. The population of this study is higher institutions in Ogun State, Nigeria while samples were picked across the three geopolitical zones of Ogun State, Nigeria, the results of the data collected were also analyzed using simple percentage and frequency table. The findings of this study reveals that Electronic communication channels effectively contributes to research, teaching and learning during election break and other stay at home periods in Nigeria. The study also concludes by recommending that apart from stay at home periods, higher institutions in Nigeria needs to have online copies of materials being taught in the class in order to aid learning as well as having video format of lecture which will enable students to have access to lecture at their dispersed location.